Anti-DLL4 VNAR targeted nanoparticles for targeting of both tumour and tumour associated vasculature. Issue 27 (6th July 2020) - Leach, Adam; Smyth, Peter; Ferguson, Laura; Steven, John; Greene, Michelle K.; Branco, Cristina M.; McCann, Aidan P.; Porter, Andrew; Barelle, Caroline J.; Scott, Christopher J.
Abstract : Anti-DLL4 VNAR targeted nanoparticles – a novel targeting ligand towards an under-investigated target. Abstract : Whilst there is an extensive body of preclinical nanomedicine research, translation to clinical settings has been slow. Here we present a novel approach to the targeted nanoparticle (NP) concept: utilizing both a novel targeting ligand, VNAR (Variable New Antigen Receptor), a shark-derived single chain binding domain, and an under-investigated target in delta-like ligand 4 (DLL4). We describe the development of an anti-DLL4 VNAR and the site-specific conjugation of this to poly(lactic- co -glycolic) acid PEGylated NPs using surface maleimide functional groups. These nanoconjugates were shown to specifically bind DLL4 with high affinity and were preferentially internalized by DLL4-expressing pancreatic cancer cell lines and endothelial cells. Furthermore, a distinct anti-angiogenic effect endowed by the anti-DLL4 VNAR was evident in in vitro tubulogenic assays. Taken together these findings highlight the potential of anti-DLL4 targeted polymeric NPs as a novel therapeutic approach in pancreatic cancer.